Stabilitas Emosi dalam Menghadapi Stres dan Perubahan Kemampuan Adaptasi Individu - Eka Sarqi Ari Frastika Tarigan (Assertive: Islamic Counseling Journal, 2025)
The purpose of this study was to investigate the influence of emotional stability on individual adaptability in dealing with stress and change, and to test the causal relationship model between variables using Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis with SmartPLS 4 software. SmartPLS 4 was chosen for its ability to process complex structural models, even when the data is not normally distributed, and is suitable for both exploratory and predictive research with small to medium sample sizes. In addition, the advantage of SmartPLS lies in its flexibility in testing latent relationships between constructs, both in reflective and formative measurement models. This study employs a quantitative approach, utilizing a survey method to collect primary data from relevant respondents. This approach is suitable for testing the relationship between variables through numerical data and objective statistical analysis. The results of this study indicate that emotional stability plays a crucial role in an individual's ability to manage stress effectively, as individuals with good emotional stability are better equipped to mitigate the negative impact of stress on their psychological well-being. In addition, high stress levels hurt adaptability, whereas an open and positive attitude towards change has a significant positive influence on enhancing adaptability. Furthermore, emotional stability serves as a mediator that links the impact of stress and change to adaptation, with partial mediation on the stress pathway and complete mediation on the change pathway.   Tujuan penelitian adalah mengetahui pengaruh stabilitas emosi dalam menghadapi stres dan perubahan terhadap kemampuan adaptasi individu, serta menguji model hubungan kausal antar variabel menggunakan analisis Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan perangkat lunak SmartPLS 4. SmartPLS 4 dipilih karena kemampuannya mengolah model struktural yang kompleks meskipun data tidak berdistribusi normal, serta cocok untuk penelitian eksploratif dan prediktif dengan ukuran sampel kecil hingga sedang. Selain itu, keunggulan SmartPLS terletak pada fleksibilitasnya dalam menguji hubungan laten antar konstruk, baik dalam model pengukuran reflektif maupun formatif. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei untuk mengumpulkan data primer dari responden yang relevan, karena pendekatan ini sesuai untuk menguji hubungan antar variabel melalui data numerik dan analisis statistik yang objektif. Hasil dalam penelitian ini menunjukkan bahwa stabilitas emosi memiliki peran penting dalam kemampuan individu mengelola stres secara efektif, dimana individu dengan kestabilan emosi yang baik mampu meredam dampak negatif stres terhadap kesejahteraan psikologis. Selain itu, tingkat stres yang tinggi berpengaruh negatif terhadap kemampuan adaptasi, sedangkan sikap terbuka dan positif terhadap perubahan memberikan pengaruh positif yang signifikan dalam meningkatkan kemampuan adaptasi. Lebih lanjut, stabilitas emosi berfungsi sebagai mediator yang menghubungkan pengaruh stres dan perubahan terhadap adaptasi, dengan mediasi parsial pada jalur stres dan mediasi penuh pada jalur perubahan.